A point light source that emits light in all directions is located at point A = ( 0 , 0 , 1 6 ) . An opaque sphere of radius 5 is centered at H = ( 1 0 , 0 , 5 ) . Find the area of the shadow of the sphere on the x y plane.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By the distance equation, A H = ( 1 0 − 0 ) 2 + ( 0 − 0 ) 2 + ( 5 − 1 6 ) 2 = 2 2 1 .
Let a tangent point on the sphere be T ( p , q , r ) . Then ∠ A T H is a right triangle and by the Pythagorean Theorem, A T = A H 2 − H T 2 = 2 2 1 2 − 5 2 = 1 4 .
By the distance equation on A H , p 2 + q 2 + ( r − 1 6 ) 2 = 1 9 6 , and by the distance equation on H T , ( p − 1 0 ) 2 + q 2 + ( r − 5 ) 2 = 2 5 . These two equations solve to p = 1 0 1 1 r + 2 and q = − 1 0 0 2 2 1 r 2 + 5 1 3 8 r − 6 4 .
The vector A T has an equation of ( x , y , z ) = ( p , q , r − 1 6 ) t + ( 0 , 0 , 1 6 ) . Setting z = 0 gives t = 1 6 − r 1 6 , so that x = 1 6 − r 1 6 p and y = 1 6 − r 1 6 q .
Substituting p = 1 0 1 1 r + 2 and q = − 1 0 0 2 2 1 r 2 + 5 1 3 8 r − 6 4 into x = 1 6 − r 1 6 p and y = 1 6 − r 1 6 q and eliminating r gives 2 4 x 2 − 8 8 0 x + 4 9 y 2 + 4 8 0 0 = 0 , which rearranges to ( 3 3 5 ) 2 ( x − 3 5 5 ) 2 + ( 3 1 0 6 ) 2 y 2 = 1 , an ellipse on the x y -plane where a = 3 3 5 and b = 3 1 0 6 .
The area of the ellipse is then A = π a b = π ⋅ 3 3 5 ⋅ 3 1 0 6 = 9 3 5 0 π 6 ≈ 2 9 9 . 2 6 .
Let P = ( x , y , ( z = 0 ) ) be a point in the x y plane. Let u = ( u x , u y , u z ) be a unit vector going from P to A . From any point within the shadow, traveling a distance α from P in the direction of u results in an intersection with the sphere. This can be expressed mathematically as:
( x + α u x − H x ) 2 + ( y + α u y − H y ) 2 + ( z + α u z − H z ) 2 = R 2
Scan through the x y plane with reasonably high spatial resolution and solve for α for each ( x , y ) . If there are real-valued solutions for α (meaning that there is an intersection with the sphere), increment the area sum by d A = d x d y . Some care must be taken to ensure that the full shadow has been accounted for.
The boundary of the shadow is the intersection of the cone whose apex is point A (the light source), and which is tangential to the sphere centered at H . So first, we'll find the semi-vertical angle of this cone.
To that end, we'll find the distance A H :
A H = 1 0 2 + 1 1 2 = 2 2 1
Therefore, the semi-vertical angle is given by:
θ = sin − 1 ( 2 2 1 5 )
from which, cos θ = 1 − 2 2 1 2 5 = 2 2 1 1 9 6
Next, we want to find the equation of the cone. Let r = ( x , y , z ) be a point on the surface of the cone, then the vector extending from point A to this point makes an angle θ with the vector A H . This means that,
( r − A ) ⋅ ∣ A H ∣ A H = cos θ ∣ r − A ∣
Now, the vector A H = ( 1 0 , 0 , − 1 1 ) = [ 1 0 , 0 , − 1 1 ] T , so in matrix notation, the above dot product is written as,
( r − A ) T ⎣ ⎡ 1 0 0 − 1 1 ⎦ ⎤ = 1 9 6 ∣ r − A ∣
Squaring,
( r − A ) T ⎣ ⎡ 1 0 0 0 − 1 1 0 0 0 0 − 1 1 0 0 1 2 1 ⎦ ⎤ ( r − A ) = 1 9 6 ( r − A ) T ( r − A )
subtracting the right hand side from the left hand side, we obtain,
( r − A ) T ⎣ ⎡ − 9 6 0 − 1 1 0 0 − 1 9 6 0 − 1 1 0 0 − 7 5 ⎦ ⎤ ( r − A ) = 0
this is the equation of the cone.
Plugging in z = 0 yields the equation of the shadow in the x y plane:
[ x , y , − 1 6 ] T ⎣ ⎡ − 9 6 0 − 1 1 0 0 − 1 9 6 0 − 1 1 0 0 − 7 5 ⎦ ⎤ ⎣ ⎡ x y − 1 6 ⎦ ⎤ = 0
Expanding this quadratic form, we obtain,
− 9 6 x 2 − 2 2 0 ( − 1 6 ) ( x ) − 1 9 6 y 2 − 7 5 ( − 1 6 ) 2 = 0
which simplifies to,
2 4 x 2 − 8 8 0 x + 4 9 y 2 + 4 8 0 0 = 0
Completing the square in x ,
2 4 ( x − 4 8 8 8 0 ) 2 − 2 4 ( 4 8 ) 2 ( 8 8 0 ) 2 + 4 9 y 2 + 4 8 0 0 = 0
So that,
2 4 ( x − 3 5 5 ) 2 + 4 9 y 2 = 3 9 8 0 0
This is the equation of the shadow ellipse in standard form; its semi-major and semi-minor axes lengths are
a = 3 ( 2 4 ) 9 8 0 0 = 3 3 5 and b = 3 ( 4 9 ) 9 8 0 0 = 1 0 3 2
Therefore, the area of the shadow is π a b = π 3 3 5 0 3 2 ≈ 2 9 9 . 2 6
Problem Loading...
Note Loading...
Set Loading...
The shadow cast is an ellipse, whose area A = π a b , where a and b are the lengths of its semi-axes. Hence we need only to find a and b . Let us do that using 2-dimensional diagrams.
Looking normal to the y z -plane, the major axis of the ellipse is B C = 2 a . Let ∠ B A H = ∠ C A H = α and ∠ O A H = β . We note that sin α = 1 0 2 + ( 1 6 − 5 ) 2 5 = 2 2 1 5 ⟹ tan α = 1 4 5 and tan β = 1 6 − 5 1 0 = 1 1 1 0 . Then O C = 1 6 tan ( β + α ) = 1 6 ⋅ 1 − 1 1 1 0 ⋅ 1 4 5 1 1 1 0 + 1 4 5 = 3 0 and O B = 1 6 tan ( β − α ) = 1 6 ⋅ 1 + 1 1 1 0 ⋅ 1 4 5 1 1 1 0 − 1 4 5 = 3 2 0 . Therefore, a = 2 3 0 − 3 2 0 = 3 3 5 .
To find b , we look at setup normal to the x y -plane. The value of b is such that the ellipse is tangent to the ray of light from A which is also tangent to the sphere. Swap the x - and y -axes for convenience. Then the equation of the ellipse is
a 2 ( x − 3 2 0 − a ) 2 + b 2 y 2 = 1 ⟹ 1 2 2 5 ( 3 x − 5 5 ) 2 + b 2 y 2 = 1
And the equation of the upper ray that is tangent to the sphere is y = 3 x . Let point on the ellipse which is tangent to this ray be P ( x , y ) . Then P ( x , y ) satisfies both equations and we have:
1 2 2 5 ( 3 x − 5 5 ) 2 + 3 b 2 x 2 = 1 . . . ( 1 )
The gradient at point P is also equal to the gradient of the ray which is 3 1 , and we have:
1 2 2 5 2 ⋅ 3 ( 3 x − 5 5 ) + b 2 2 y ⋅ d x d y 1 2 2 5 3 ( 3 x − 5 5 ) + 3 b 2 x 1 2 2 5 3 x ( 3 x − 5 5 ) + 3 b 2 x 2 1 2 2 5 ( 3 x − 5 5 ) ( 3 x − 5 5 − 3 x ) 1 1 ( 5 5 − 3 x ) ⟹ x ⟹ b = 0 = 0 = 0 = 1 = 2 4 5 = 1 1 1 2 0 = 1 0 3 2 Putting y = 3 x and d x d y = 3 1 Multiply both sides by x Subtract from ( 1 ) Substitute it in ( 1 )
Therefore the area of the shadow A = π a b = π ⋅ 3 3 5 ⋅ 1 0 3 2 ≈ 2 9 9 .